2005
DOI: 10.2138/rmg.2005.58.8
|View full text |Cite
|
Sign up to set email alerts
|

Fission-track Analysis of Detrital Zircon

Abstract: INTRODUCTIONZircon has become one of the most important minerals for studying sediment provenance and the exhumation history of orogenic belts. The reason for this utility is that zircon is common in many igneous, metamorphic, and sedimentary rocks, it is resistant to weathering and abrasion, and it can be dated with various isotopic methods having reasonable high concentrations of uranium and thorium (Fig. 1). Techniques used to date detrital zircon include U/Pb and (U-Th)/He dating, but in this chapter we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 62 publications
1
147
0
5
Order By: Relevance
“…Previous studies show that many factors (including radiation damage, U concentration, time, temperature, cooling rate, and pressure) can affect the annealing properties of ZFT (Bernet and Garver 2005). Of these factors, radiation damage has the greatest effect.…”
Section: Zircon Fission-track Resultsmentioning
confidence: 99%
“…Previous studies show that many factors (including radiation damage, U concentration, time, temperature, cooling rate, and pressure) can affect the annealing properties of ZFT (Bernet and Garver 2005). Of these factors, radiation damage has the greatest effect.…”
Section: Zircon Fission-track Resultsmentioning
confidence: 99%
“…As a reference, Tagami and Shimada (1996) have shown that zircon fission track ages in sandstones surrounding a rapidly cooled granitic intrusion become totally reset within a distance of ~3 km from a steep-dipping contact, although this distance can vary depending on several factors, including the size and shape of the intrusives, the permeability of the wallrock, the depth of emplacement, and the presence of fluids (e.g., Adriasola et al, 2006). The zircon fission track ages are interpreted to represent the time of post-emplacement cooling to temperatures of around 280±30°C (e.g., Tagami and Shimada, 1996;Bernet and Garver, 2005;Reiners and Brandon, 2006), and the biotite 40 Ar/ 39 Ar closure temperature can be estimated as 320±30°C using Dodson (1973) and parameters presented by Harrison et al (1985) and McDougall and Harrison (1999). Therefore, the overall coincidence of the zircon fission track ages with biotite 40 Ar/ 39 Ar ages (Table 4) is consistent with in situ post-magmatic rapid cooling of the host intrusions.…”
Section: Resultsmentioning
confidence: 99%
“…However, experimental data show that there is a wide temperature range, from 160 to 380°C, for the temperature bounds for the zircon partial annealing zone, which are strongly dependent on cooling rates and alpha radiation damage of zircon crystals (Bernet and Garver, 2005;Tagami, 2005;Reiners and Brandon, 2006). Thus, as a reasonable approximation for this work, a temperature of 280±30°C has been plotted against the zircon fission track age in study to produce a single temperature-time point on a thermal history path (e.g., Tagami and Shimada, 1996;Thomson et al, 2001;Reiners and Brandon, 2006;Adriasola and Stökhert, 2008).…”
Section: Fission Track Thermochronologymentioning
confidence: 99%
“…The key finding is that samples from the Seward-Malaspina glacier have a significant fraction of ZFT ages of <3 Myr, whereas samples farther west have increasingly larger percentages of older ages (>6 Myr). Analysis of these data using binomial peak-fitting routines 15 yields age populations for each sample. A remarkable aspect of the cooling ages in the Seward-Malaspina samples is that single-grain ZFT ages are as young as 0.4 Myr and define an age-population peak at 2-3 Myr that comprises 25-41% of the dated grains.…”
mentioning
confidence: 99%